Collaborative Testing Improves Performance but Not Content Retention in a Large-Enrollment Introductory Biology Class - Leight, Hayley (American Society for Cell Biology, 2012)
Collaborative testing has been shown to improve performance but not always content retention. In this study, we investigated whether collaborative testing could improve both performance and content retention in a large, introductory biology course. Students were semirandomly divided into two groups based on their performances on exam 1. Each group contained equal numbers of students scoring in each grade category (“A”–“F”) on exam 1. All students completed each of the four exams of the semester as individuals. For exam 2, one group took the exam a second time in small groups immediately following the individually administered test. The other group followed this same format for exam 3. Individual and group exam scores were compared to determine differences in performance. All but exam 1 contained a subset of cumulative questions from the previous exam. Performances on the cumulative questions for exams 3 and 4 were compared for the two groups to determine whether there were significant differences in content retention. Even though group test scores were significantly higher than individual test scores, students who participated in collaborative testing performed no differently on cumulative questions than students who took the previous exam as individuals.